2022
DOI: 10.1161/circulationaha.121.054976
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Sinoatrial Node Dysfunction in Heart Failure With Preserved Ejection Fraction

Abstract: Background: The ability to increase heart rate (HR) during exercise and other stressors is a key homeostatic feature of the sinoatrial node (SAN). When the physiologic HR response is blunted, chronotropic incompetence limits exercise capacity, a common problem in patients with heart failure (HF) and preserved ejection fraction (HFpEF). Despite its clinical relevance, the mechanisms of chronotropic incompetence remain unknown. Methods: Dahl salt-sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 64 publications
1
16
1
Order By: Relevance
“…In a rat model of heart failure with preserved ejection fraction, scRNAseq transcriptome analyses of the sinoatrial node revealed significant alterations in both the “membrane clock” (ion channels) and the “calcium clock” (spontaneous calcium release events) which—when probed in functional experiments—further validated RNA-seq data ( 117 ).…”
Section: Discussionmentioning
confidence: 77%
“…In a rat model of heart failure with preserved ejection fraction, scRNAseq transcriptome analyses of the sinoatrial node revealed significant alterations in both the “membrane clock” (ion channels) and the “calcium clock” (spontaneous calcium release events) which—when probed in functional experiments—further validated RNA-seq data ( 117 ).…”
Section: Discussionmentioning
confidence: 77%
“…LV, left ventricle; bpm, beats per minute (See figure on next page.) exercise (chronotropic incompetence) and a functional limitation to further sinus node activation during exercise (sinoatrial node dysfunction) would explain at least in part this impaired exercise capability [57,58]. These features have also been recently observed in preclinical models of HF [57].…”
Section: Stress Echocardiography and Electrocardiographymentioning
confidence: 89%
“…exercise (chronotropic incompetence) and a functional limitation to further sinus node activation during exercise (sinoatrial node dysfunction) would explain at least in part this impaired exercise capability [57,58]. These features have also been recently observed in preclinical models of HF [57]. To assess the degree of heart rate increase following stimulation in mice, the β-adrenergic agonist isoproterenol is injected intraperitoneally (1-2 mg/kg body weight) during ECG acquisition [56].…”
Section: Stress Echocardiography and Electrocardiographymentioning
confidence: 99%
“…Whole-cell electrophysiology recordings were performed as we previously described 43 Experiments were carried out using standard microelectrode amphotericin B-perforated whole-cell patch-clamp with an Axopatch 200B amplifier (Molecular Devices) with a sampling rate of 20 kHz and low-pass filtered at 5 kHz. Experiments were performed at 36 ± 1°C with cells perfused with an extracellular Tyrode’s solution containing (mM): 140 NaCl, 5 KCl, 1.8 CaCl2, 1 MgCl2, 10 glucose, and 10 HEPES, pH 7.4 NaOH.…”
Section: Methodsmentioning
confidence: 99%